The Close Connection of Body and Mind (KULT_online, 2009)
In the present volume, neurophysiologist Giacomo Rizzolatti and philosopher of science Corrado Sinigaglia give an overview of realms of neurology and cognitive science that directly concern the sociality and communication of human beings – and therefore also touch upon basic issues in the humanities. The central points are the understanding of and acting within the space of everyday life, the understanding of actions in general and, finally, the emergence of language. To explain these phenomena, the authors attribute great importance to the close interlocking of brain areas that function in perception with those that function in controlling action, as well as to the existence of neural systems that are activated both in observing and in executing an act (so-called mirror neurons).